Motivations for knowledge sharing in virtual social networks: a comparative study between Brazil and France - Martins, Daniel Finamore (2012)
Post-modern societies are characterized by the transition from material to knowledgebased economies, where the humanity is facing a growing connectivity but, at the same time, the weakening of social structures that creates an increasing need for cognitive and affective bases for life (Rheingold, 1992; Wasko & Farah, 2005; Arvidsson, 2008) In this scenario is the phenomenon of virtual social networks that is putting together millions of individuals exchanging text-based messages, images, and videos everyday (Nielsen, 2012), and organizations investing more and more to engage in those new trends (McWilliam, 2000; Reichheld & Schefter, 2000; Yoo, Suh & Lee, 2002; Arvidsson, 2008). Consequently, one of the most important questions that arises and gains importance for academics and practitioners is: why people share? (Monge, Fulk, Kalman, Flanigan, Parnassa & Rumsey, 1998; Lin, 2001) Based on a multi case methodology approach developed in Brazil and France, this study aims to produce a significant theoretical review, bring relevant insights from different contexts, and propose a model for assessing the main motivations for knowledge sharing in virtual social networks. They were systematized in five main dimensions: structural, cognitive, and relational capital reasons, personal motivations, and monetary reasons (Nahapiet & Ghoshal, 1998; Wasko & Faraj, 2005; Chiu et al, 2006). The findings suggest that the process of knowledge sharing in virtual networks seems to be consequence of a combination of community and self-oriented motivations that vary slightly according to different goals and contexts of these online communities, where monetary reasons seem to be secondary.